Stargazer - Gray, Claudia (New York HarperTeen, 2009)
Teenage vampire Bianca finds herself the target when evil wraiths attack her boarding school, Evernight Academy
1
Keywords: Boarding schools -- Fiction; Horror stories; Schools -- Fiction; Vampires -- Fiction